Urgency of Law Enforcement of Law Number 41 of 2004 about Wakaf in the Perspective of Islamic Law Principles - Neneng Hasanah (International Journal of Nusantara Islam, 2018)
Islam is present as a blessing for all nature and its contents. Islam is the solution to the problems faced by humanity, especially as a guide and a mercy for those who believe. The solution given by Islam is the grace of al-mashlahah (benefit) living in the world and the hereafter. Reviewers of Islamic law can ensure that Islamic law is built for human benefit, preventing damage and realizing the main good. The contribution of Islamic law principles in managing people's lives is undeniable. In history it was recorded, that before Islam came and was brought by the Prophet Muhammad (PBUH), the state of the pitch-black world marked by the behavior of Jahiliyah at that time. Then the Prophet (PBUH) came with the light of Islam and his teachings which up to now still have the purity of teaching and its benefits in personal life and society in general. The form of real contribution in the benefit of the people, is in the teachings of Sadaqah Jariyah in the form of waqf. In the teachings / command of the implementation of waqf contained several principles of Islamic law, among others: the principle of amar maruf nahi munkar, justice and the principle of al-ta'awun.